The Role of Stigma in the Nursing Care of Families Impacted by Neonatal Abstinence Syndrome. (October 2020) - Recto, Pamela; McGlothen-Bell, Kelly; McGrath, Jacqueline; Brownell, Elizabeth; Cleveland, Lisa M.
Abstract : Background: The current US opioid crisis has resulted in a significant increase in opioid use disorder among pregnant and parenting women. Substance use disorders, in general, are highly stigmatized conditions. Stigma serves as a well-documented global barrier to health-seeking behaviors and engagement in healthcare. While extensive research exists on the stigma of mental illness, few studies have explored the stigma experienced by families impacted by neonatal abstinence syndrome (NAS). Purpose: Therefore, the purpose of this article is to explore the role of stigma in the care of families impacted by NAS. Methods: In this article, we present a discussion about the effects of stigma on this patient population and provide exemplars of stigma experiences from our previous research and the existing literature. Findings/Results: Mothers of infants with NAS faced the challenges of overcoming stigma as they were often ostracized, excluded, and shamed. Nurses who provide care for these women and their infants have reported experiencing ethical distress, moral distress, and compassion fatigue. Implications for Practice: Greater awareness of the impact of opioid use on the maternal–child population has resulted in numerous educational offerings for healthcare providers; however, this alone is not adequate to end stigma. Fortunately, promising tools and methods have been developed for assisting nurses with addressing stigma in a manner that can be both nonconfrontational and highly effective. Implications for Research: Future research is needed to explore and evaluate the efficacy of various existing strategies for counteracting harmful stigma in this patient population.